Correlating Cleaning Thoroughness with Effectiveness and Briefly Intervening to Affect Cleaning Outcomes: How Clean Is Cleaned? - Robert Clifford; Michael Sparks; Eve Hosford; Ana Ong; Douglas Richesson; Susan Fraser; Yoon Kwak; Sonia Miller; Michael Julius; Patrick McGann; Emil Lesho (PLoS ONE, 2016)
Objectives The most efficient approach to monitoring and improving cleaning outcomes remains unresolved. We sought to extend the findings of a previous study by determining whether cleaning thoroughness (dye removal) correlates with cleaning efficacy (absence of molecular or cultivable biomaterial) and whether one brief educational intervention improves cleaning outcomes. Design Before-after trial. Setting Newly built community hospital. Intervention 90 minute training refresher with surface-specific performance results. Methods Dye removal, measured by fluorescence, and biomaterial removal and acquisition, measured with culture and culture-independent PCR-based assays, were clandestinely assessed for eight consecutive months. At this midpoint, results were presented to the cleaning staff (intervention) and assessments continued for another eight consecutive months. Results 1273 surfaces were sampled before and after terminal room cleaning. In the short-term, dye removal increased from 40.3% to 50.0% (not significant). For the entire study period, dye removal also improved but not significantly. After the intervention, the number of rooms testing positive for specific pathogenic species by culturing decreased from 55.6% to 36.6% (not significant), and those testing positive by PCR fell from 80.6% to 53.7% (P = 0.016). For nonspecific biomaterial on surfaces: a) removal of cultivable Gram-negatives (GN) trended toward improvement (P = 0.056); b) removal of any cultivable growth was unchanged but acquisition (detection of biomaterial on post-cleaned surfaces that were contaminant-free before cleaning) worsened (P = 0.017); c) removal of PCR-based detection of bacterial DNA improved (P = 0.046), but acquisition worsened (P = 0.003); d) cleaning thoroughness and efficacy were not correlated. Conclusion At this facility, a minor intervention or minimally more aggressive cleaning may reduce pathogen-specific contamination, but not without unintended consequences.